An improved image registration technique for shape reconstruction - Roy, Biprojit; Oishe, Geetanjali (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.